GUÁNUCOS OCCUPATION FROM MIDDLE HORIZON PERIOD TO LATE INTERMEDIATE - Onofre Mayta, José A. (2012)
The Upper Marañón witnessed some of the cultural groups that had a prolonged occupation. Here we board on one of them, the Guanuco, which have been analyzed on the part of historians have been mistaken as part of an alleged Yarowilca Empire, which has led to misperceptions of what were really: a nation different independent entities, following anthropological theory, equate it with headquarters, related to a deep cultural identity defined through their settlements and furniture materials. For this proposal we use the information from its extensive field settlements with different types of architecture that demonstrate successive structural changes without changing the place of residence.